PENGARUH WAKTU DAN LUAS PERMUKAAN TERHADAP KETEBALAN PRODUK PADA ELEKTROPLATING ACID ZINC - Irman .; Budhi .; Faevi .; Iis . (Jurnal Ilmiah Teknik Kimia, 2017)
This research  using Faraday’s law to analize result of measurements. There are 2  parameters varying  in research, the surface area of specimen  ( 6 x 10 cm², 6 x 5 cm² and 5 x 3  cm²) and time  ( 6, 9 and 12 minutes). The research method was done  by electroplating scheme consists of a cathode, anode, electrolyte, which is coupled with a DC electrical current that is placed on Hull Cell. The purpose of research is to determine impact of extent of time and amount of  surface area of specimen to layer thickness occured from the acid zinc electroplating methods. The result of  research obtained is the greater of surface area  will form specimen mass and layer smaller, and the longer of  electroplating process time will form  speciment mass and layer increasing thickerKeywords : Electroplating, Acid Zinc